An impact-insensitive fiber optic current transformer based on polarization maintaining photonic crystal fiber delay coil - Gao, Hongze; Wang, Guochen; Gao, Wei; Zhao, Bo; Zhang, Runfeng; Zhang, Boya; Yang, Fan (Frontiers in Physics, 2023)
When the polarization maintaining fiber (PMF) delay coil of a fiber optic current transformer (FOCT) is impacted, external forces on the optical fibers and change of their birefringence may lead to extra phase errors during the propagation of optical signals in the fibers. These errors increase the error in current measurement. In the paper, the environmental impact mechanisms influencing the PMF delay coil of FOCT were investigated with a mathematical error model. The method of replacing PMF with a polarization-maintaining photonic crystal fiber (PCF) as the delay coil was proposed. Also, the relationship of structural parameters of air holes and linear birefringence of the polarization maintaining PCF subjected to stress was investigated. The structural parameters of optical fibers were also optimized subsequently. Simulated impact experiments of FOCT with polarization maintaining PCF and PMF as the delay coil, respectively, demonstrated the effective impact resistance of FOCT with polarization-maintaining PCF delay coil after the optimization of its structural parameters. The current measurement errors of the FOCTs with polarization maintaining PCF delay coil reduced by approximately 35% with respect to the FOCT with PMF delay coil.